The complete chloroplast genome of an endangered species in Korea, Halenia corniculata (L.) Cornaz (Gentianaceae) - Jongsun Park; Narae Yun; Sang-Hun Oh (Mitochondrial DNA. Part B. Resources, 2019)
Halenia corniculata, characterized by having yellow corollas with spurs at the base within Halenia, is an endangered species in Korea, which represents the southern limit of the distribution range of the species. We present the complete chloroplast genome of H. corniculata. Its length is 153,198 bp and it has four subregions; 83,252 bp of large-single-copy and 18,372 bp of small-single-copy regions are separated by 25,787 bp of inverted repeat, including 130 genes (85 protein-coding genes, 8 rRNAs, and 37 tRNAs). Phylogenetic trees show that H. corniculata is a sister to S. bimaculata, nested within Swertia, consistent with previous phylogenetic studies.